Tinjauan kritis implementasi ham di indonesia berdasarkan sila keempat dan kelima : studi pancasila dan penegakan hak asasi manusia - rosyyidin_26, Rosyyidin (Maliki Interdisciplinary Journal, 2025)
Human Rights (HAM) are the fundamental rights enjoyed by every human being by virtue of their dignity as a person. These rights are not granted by society or the state but are inherent simply because one is human. This study discusses and examines the implementation of Human Rights (HAM) in Indonesia by focusing on their relevance to the values of Pancasila, particularly the fourth and fifth principles. The fourth principle emphasizes the concept of democracy guided by the inner wisdom of deliberation and representation, which essentially teaches the proper and lawful practice of democracy. Meanwhile, the fifth principle underscores the importance of social justice for all Indonesian people. These two principles serve as philosophical foundations that guide the state in formulating policies and upholding human rights in Indonesia.The research method used is qualitative, employing a literature study approach. Data were collected and cited from books, academic journals, laws and regulations, as well as official government documents relevant to human rights and Pancasila in Indonesia. The analysis was conducted by examining the alignment between Pancasila principles and the actual implementation of human rights in Indonesia, then evaluating the ongoing challenges faced by Indonesian society in the political, social, and legal spheres.The results show that, normatively, Indonesia already possesses a strong legal framework, including the 1945 Constitution and Law No. 39 of 1999 on Human Rights. However, in practice, the implementation of human rights still faces serious obstacles. In terms of democracy, public participation often remains procedural, while substantial participation space is still very limited. On the other hand, the principle of social justice has not been fully realized due to economic inequality, discrimination against minority groups, and weak law enforcement caused by certain law enforcers who misuse their authority for personal interests. The conclusion of this study emphasizes that the implementation of human rights in Indonesia still requires strengthening and improvement both institutionally and culturally in political behavior.